Phenylalanine 4-Hydroxylase Contributes to Endophytic Bacterium Pseudomonas fluorescens’ Melatonin Biosynthesis - Jiao, Jian; Xia, Yan; Zhang, Yingli; Wu, Xueli; Liu, Chonghuai; Feng, Jiancan; Zheng, Xianbo; Song, Shangwei; Bai, Tuanhui; Song, Chunhui; Wang, Miaomiao; Pang, Hongguang (Frontiers in Genetics, 2021)
Melatonin acts both as an antioxidant and growth regulatory substance in plants. Pseudomonas fluorescens endophytic bacterium has been shown to produce melatonin and increase plant resistance to abiotic stressors through increasing endogenous melatonin. But in bacteria, genes are still unknown to melatonin-related. This work reports that the bacterial phenylalanine 4-hydroxylase (PAH) likely contributes to the 5-hydroxytryptophan (5-HTP) biosynthesis and further affects the subsequent production of melatonin in P. fluorescens. The purified PAH protein of P. fluorescens not only hydroxylated phenylalanine but also exhibited l-tryptophan (l-Trp) hydroxylase activity by converting l-Trp to 5-HTP in vitro.. However, baterial PAH displayed lower activity and affinity for l-Trp than l-phenylalanine. Notably, the PAH deletion of P. fluorescens blocked melatonin production by causing a significant decline in 5-HTP levels and thus decreased the resistance to abiotic stress. Overall, this study reveals a possible role for bacterial PAH in controlling 5-HTP and melatonin biosynthesis in bacteria, and expands the current knowledge of melatonin production in microorganisms.